Bedside interpretation of cerebral energy metabolism utilizing microdialysis in neurosurgical and general intensive care - Nordström, Carl-Henrik; Forsse, Axel; Jakobsen, Rasmus Peter; Mölström, Simon; Nielsen, Troels Halfeldt; Toft, Palle; Ungerstedt, Urban (Frontiers in Neurology, 2022)
The microdialysis technique was initially developed for monitoring neurotransmitters in animals. In 1995 the technique was adopted to clinical use and bedside enzymatic analysis of glucose, pyruvate, lactate, glutamate and glycerol. Under clinical conditions microdialysis has also been used for studying cytokines, protein biomarkers, multiplex proteomic and metabolomic analyses as well as for pharmacokinetic studies and evaluation of blood-brain barrier function. This review focuses on the variables directly related to cerebral energy metabolism and the possibilities and limitations of microdialysis during routine neurosurgical and general intensive care. Our knowledge of cerebral energy metabolism is to a large extent based on animal experiments performed more than 40 years ago. However, the different biochemical information obtained from various techniques should be recognized. The basic animal studies analyzed brain tissue homogenates while the microdialysis technique reflects the variables in a narrow zone of interstitial fluid surrounding the probe. Besides the difference of the volume investigated, the levels of the biochemical variables differ in different compartments. During bedside microdialysis cerebral energy metabolism is primarily reflected in measured levels of glucose, lactate and pyruvate and the lactate to pyruvate (LP) ratio. The LP ratio reflects cytoplasmatic redox-state which increases instantaneously during insufficient aerobic energy metabolism. Cerebral ischemia is characterized by a marked increase in intracerebral LP ratio at simultaneous decreases in intracerebral levels of pyruvate and glucose. Mitochondrial dysfunction is characterized by a moderate increase in LP ratio at a very marked increase in cerebral lactate and normal or elevated levels of pyruvate and glucose. The patterns are of importance in particular for interpretations in transient cerebral ischemia. A new technique for evaluating global cerebral energy metabolism by microdialysis of the draining cerebral venous blood is discussed. In experimental studies it has been shown that pronounced global cerebral ischemia is reflected in venous cerebral blood. Jugular bulb microdialysis has been investigated in patients suffering from subarachnoid hemorrhage, during cardiopulmonary bypass and resuscitation after out of hospital cardiac arrest. Preliminary results indicate that the new technique may give valuable information of cerebral energy metabolism in clinical conditions when insertion of an intracerebral catheter is contraindicated.